PENGARUH LEVEL PUPUK BOKASHI KOTORAN AYAM TERHADAP PERTUMBUHAN SORGUM BROWN MID RIB (BMR) - Bandu, Vivi S; Kaligis, D A; ., Rustandi .; Kaunang, W B (ZOOTEC, 2018)
EFFECT OF BOKASHI FERTILIZER LEVEL CHICKEN MANURE ON THE GROWHTH OF BROWN MID RIB (BMR) SORGHUM. The purpose of the present research was to determine effect of bokashi fertilizer level chicken manure on the growhth of brown mid rib (bmr) sorghum. The research was used in a completely randomized design arrangement, with 4 treatments and 7 replications. Treatments were formulated as follow : b1 = 0 g/polybag, b2 = 200 g/polybag, b3 = 400 g/polybag, b4 = 800 g/polybag. Parameters measured were : plant height, number of leaves length of leaves. Research result showed that, bokashi fertilizer of chicken manure gave a significant different (p<0,05) on plant height, number of leaves leaves length of brown mid rib sorghum. Based on the research result, it can be concluded that, the utilization of bokashi fertilizer level chicken manure with 200 g/polybag, enough to support the growth of plant height, number of leaves and leaves length of brown mid rib sorghum.Keywords : Bokashi Fertilizer Level Chicken Manure, Brown Mid Rib Sorghum, Growth.